ANALISIS TIANG PANCANG SEBAGAI DINDING PENAHAN TANAH DI DAERAH ALIRAN SUNGAI MENGGUNAKAN PROGRAM PYWALL - Amelinda Jocelin; Chaidir Anwar Makarim (JMTS: Jurnal Mitra Teknik Sipil, 2020)
Construction failure may occur due to various things. One of them is used a shallow foundation for a retaining wall. It can possible, but consider environmental condition where there is a heavy flow of water along the wall. Therefore it is necessary to use a deep foundation. Pile are printed concrete products. It is used to support a load and distribute the load to the subgrade. This pile is also equipped with iron reinforcement so that it can guarantee the quality and strength. This calculation is using a closed-form solution. The software used is P-Y Wall which fixes a flexible retaining wall or pile/drill wall. This program will calculate pile deflection, shear forces, and bending moments. In this assessment, variations were made relating to the distance between the piles and the values of L1 and L2. L1 shows the free long pile and L2 shows the long pile entering the ground. Variation 3A with the distance between the piles 100 cm and the length of the pile 15 m. The average value of L1 was 10.8 m for the value and the value of L2 was 4.2 m. Both of deflection and moment can fulfill the qualification, the value is 9,1 m (from 10,8 m) dan 320 kNm (from 399 kN/m).